Implementation of Religious Culture to Develop Children’s Character in Early Childhood Education - Pamuji, Zuri; Roqib, Moh.; Basit, Abdul; Yahya, M. Slamet (JURNAL PENDIDIKAN USIA DINI, 2024)
Efforts to develop children's character based on the application of religious culture are important for every early childhood education institution, but the implementation patterns are still limited. This research aims to describe the application of religious culture in early childhood education institutions in cultivating character to find application patterns. This research uses a qualitative descriptive method with a single case study design conducted at one of the early childhood education institutions in Banyumas, Indonesia. Data search was carried out using interviews, observation, and documentation. Analysis techniques used, data reduction, data presentation, verification, and conclusion. The research results show that the application of religious culture has two main parts. The part related to the phasing pattern of cultivating religious values and the part related to various religious cultures and how to transmit them to children. The phasing pattern of cultivating religious values in children is carried out through introduction and training, which leads to habituation. Meanwhile, various religious cultures include cultures related to holy books, religious rituals, and places of worship. Religious culture is transmitted through the learning process and activities outside the learning process, including socialization, role modeling, and building communication between parents and institutions. Keywords: religious culture, character, early childhood References: Abdurohim, Rohimah, B., & Hayani, R. A. (2021). Fungsi Ibadah Ritual Dalam Pembentukan Karakter Islami. Jurnal Pendidikan Karakter"Jawara" (JPKJ), 7, 74. https://jurnal.untirta.ac.id/index.php/JAWARA/article/view/11610 Abshor, M. U. (2019). Resepsi al-qur’an masyarakat gemawang mlati yogyakarta. Qof, 3(1), 41–54. https://doi.org/https://doi.org/10.30762/qof.v3i1.1022 Adhar, In’am, A., & Hartiningsih, S. (2018). Penanaman Nilai-Nilai Karakter Pada Anak Usia Dini Di Ra Al Mashitoh Tegalgondo Karangploso Malang. Jurnal Kebijakan Dan Pengembangan Pendidikan, 6(1), 232–242. https://doi.org/https://doi.org/10.22219/jkpp.v6i2.11618 Akyuni, Q. (2022). Penerapan Budaya Religius di TK/Paud. Jurnal Tarbiyatul Aulad, 7(1). https://ojs.serambimekkah.ac.id/AULAD/article/view/4792 Alhosani, N. (2022). The Influence of Culture on Early Childhood Education Curriculum in the UAE. ECNU Review of Education, 5(2), 284–298. https://doi.org/10.1177/20965311221085984 Amelia, S. W. (2021). Masjid Agung Tuban : Studi Tentang Fungsi Dalam Kehidupan Sosial Kemasyarakatan 2004-2020. Journal of Islamic History, 1(1), 46–65. https://doi.org/https://doi.org/10.53088/jih.v1i1.103 Anazifa, Z. R. A. D. (2018). Impact Of Character Education Implementation: A Goal-Free Evaluation. Problems of Education in 21st Century, 76(6), 881–899. https://www.ceeol.com/search/article-detail?id=941189 Angraeni, D. K. (2020). Peran Wanita Dalam Ajaran Agama Hindu. Bawi Ayah: Jurnal Pendidikan Agama Dan Budaya Hindu, 11(2), 54–69. https://doi.org/https://doi.org/10.33363/ba.v11i2.444 Apendi, A. T. (2021). Analisis Dampak Negatif Pergaulan Anak Remaja di Era Globalisasi Dengan Kemajuan Teknologi. Wacana Akademika: Majalah Ilmiah Kependidikan, 5(1), 26. https://doi.org/10.30738/wa.v5i1.9418 Apino, Z. R. A. (2018). Strategy and Implementation of Character Education in Senior High Schools and Vocational High Schools. Journal of Social Studies Education Research, 9(3), 370–397. https://jsser.org/index.php/jsser/article/view/294/287 Asbari, S. S. A. (2022). The Role of Islamic Religious Education in Forming the Religious Character of Students. Journal of Information Systems and Management, 1(2). https://doi.org/https://doi.org/10.4444/jisma.v1i1.1 Azmi, M. U. (2015). Implementasi Pendidikan Karakter Melalui Budaya Religius di Madrasah Tsanawiyah Mualimin Nahdlatul Wathan Pancor Lombok Timur [UIN Maulana Malik Ibrahim]. http://etheses.uin-malang.ac.id/10222/ Beyers, J. (2017). Religion and culture: Revisiting a close relative. HTS Teologiese Studies / Theological Studies, 73(1), 1–9. https://doi.org/10.4102/hts.v73i1.3864 Breen, M. M. J. R. (2016). A Dynamic Model of Cultural Reproduction. American Journal of Sociology, 121(4), 1079–1115. https://doi.org/https://doi.org/10.1086/684012 Burbules, N. (2019). Watch It; The Risks And Promises Of Information Technologies For Education. Routledge. https://doi.org/https://doi.org/10.4324/9780429503153 Dolorosa, E. (2021). Pemahaman dan Kesadaran Orang Muda Kaatolik akan Pentingnya Sharing Kitab Suci bagi Perkembangan Iman di STASI Yesus Maria Yosep Paroki Santo Yosep Pekerja Penfui Keuskupan Agung Kupang. Jurnal Pastoralia, 2(2), 10–27. https://www.pastoralia.net/index.php/pastoralia/article/view/64 Estivalèzes, M. (2017). The professional stance of ethics and religious culture teachers in Québec. British Journal of Religious Education, 39(1), 55–74. https://doi.org/10.1080/01416200.2015.1128389 Fadlilah, M. (2016). Penanaman Nilai-nilai Karakter Pada Anak Usia Dini Melalui Permainan Edukatif. Seminar Nasional PPKN, 1–7. http://eprints.umpo.ac.id/2019/ Fatimah. (2021). Implementasi Budaya Religius dalam Membina Akhlak Siswa di MI Rahmatullah Kota Jambi. Jurnal Pendidikan Guru, 2(1), 68–78. https://doi.org/https://doi.org/10.47783/jurpendigu.v2i1.189 Fitriyani, D. (2016). Manajemen Budaya Religius dalam Pembentukan Karakter Anak Usia Dini (Studi Kasus di TK Muslimat NU 07 Bahrul Ulum Desa Pucangrejo Kecamatan gemuh Kabupaten Kendal) [UIN Walisongo Semarang]. http://eprints.walisongo.ac.id/id/eprint/6654/ Hasbi, M. (2020). Pedoman Penguatan Pendidikan Karakter Pada Pendidikan Anak Usia Dini. Kemendikbud. Hendarman, E. a. (2018). Konsep dan Pedoman Penguatan Pendidikan Karakter. Kemendikbud. Isnaini, M. (2013). Internalisasi Nilai-Nilai Pendidikan Karakter Di Madrasah. Al-Ta Lim Journal, 20(3), 445–450. https://doi.org/10.15548/jt.v20i3.41 Jacobus, E. C. H. (2017). Implementasi Pendidikan Karakter Melalui Keteladanan dan Pembiasaan. JPDI (Jurnal Pendidikan Dasar Indonesia), 1(2), 25. https://doi.org/10.26737/jpdi.v1i2.262 Permendikbud Nomor 20 Tahun 2018, 12 (2018). Krogstad, K. (2017). Religious Festivals in Early Childhood Education and Care (ECEC) Institutions: A Norwegian Case Study. Journal of Nordic Early Childhood Education Research, 16(3). https://doi.org/10.7577/nbf.2158 Maarif, M. A., Wardi, M., & Amartika, S. (2020). The Implementation Strategy of Religious Culture in Madrasah. Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 6(02), 163. https://doi.org/10.32678/tarbawi.v6i02.2962 Mailani, I. S. A. (2023). Analisis Faktor Penyebab Kesulitan Siswa Dalam Pembelajaran Tematik Dengan Menggunakan Metode Miles Dan Huberman Di Kelas IV Sd Negeri 060800 Medan Area. Innovative: Journal Of Social Science Research, 3(2). https://doi.org/https://doi.org/10.31004/innovative.v3i2.1130 Mardiyati, Y. Y. I. (2014). Model Pembelajaran Berlatar Budaya Lokal Untuk Meningkatkan Interaksi Pedagogis Guru dan Siswa Taman Kanak-kanak di Kecamatan Pontianak Timur. https://repository.iainptk.ac.id/download/model-pembelajaran-berlatar-budaya-lokal-untuk-meningkatkan-interaksi-pedagogis-guru-dan-siswa-taman-kanak-kanak-di-kecamatan-pontianak-timur/ Marini, A. (2017). Character Building Through Teaching Learning Process: Lesson in Indonesia. PONTE International Scientific Researchs Journal, 73(5). https://doi.org/10.21506/j.ponte.2017.5.43 Mathews; S.Arulsamy, S. M. (2020). Role of Education in Transmitting Culture in Society. Munif, M. (2017). Strategi Internalisasi Nilai-nilai PAI dalam Membentuk Karakter Siswa. Edureligia, 1(1). https://doi.org/https://doi.org/10.33650/edureligia.v1i2.49 Mutawakkil, M. A. (2022). Pesan Perdamaian Dalam Kitab Suci Enam Agama Di Indonesia Dan Solusi Atas Konflik Agama Di Tengah Masyarakat. Journal Scientific of Mandalika, 3(8), 194–208. https://doi.org/https://doi.org/10.36312/%20(jsm).v3i8.807 Nida, T. (2019). A lesson plan model for character education in primary education. Educational Research and Reviews, 14(4), 130–139. https://doi.org/10.5897/err2018.3616 Nur, I. (2022). Transmisi Budaya Islami Pada Lembaga Formal: Studi Kasus di SDIT Al-Izzah Kota Sorong Papua Barat, Indonesia. Dayah: Journal of Islamic Education, 5(1), 53–74. https://doi.org/http://dx.doi.org/10.22373/jie.v5i1.8377 Nurrahman, A. R. T. Y. (2023). Fungsi Masjid Sebagai Tempat Ibadah dan Pusat Ekonomi Umat Islam. Jurnal Religion: Jurnal Agama, Sosial, Dan Budaya, 1(4), 372–382. https://doi.org/https://doi.org/10.55606/religion.v1i4.241 Purwanto, E. S. C. N. A. (2017). Pengembangan Nilai-nilai Karakter Anak Usia Dini Melalui Pembiasaan dan Keteladanan. Jurnal Pendidikan Anak, 2(2), 2013–2213. https://doi.org/10.26877/jo.v4i2.4005 Rachmadyanti, P. (2017). Penguatan Pendidikan Karakter Bagi Siswa Sekolah Dasar Melalui Kearifan Lokal. Jurnal Pendidikan Sekolah Dasar, 3(2), 201. https://doi.org/10.30870/jpsd.v3i2.2140 Rahardjo, M. (2017). Studi Kasus Dalam Penelitian Kualitatif: Konsep dan Prosedurnya. Rahmawati, O. (2020). Peran Guru PAUD dalam Mewujudkan Budaya Religius di PAUD Taman Asuh Anak Muslim (TAAM) Al-Qur’an Jabalkat Sambijajar Sumbergempol Tulungagung [IAIN Tulungagung]. http://repo.uinsatu.ac.id/21896/ Rahmayati, M. S. C. P. T. (2022). Strategi Dalam Menjaga Keabsahan Data Pada Penelitian Kualitatif. Jurnal Al ‘Adad: Jurnal Tadris Matematika, 1(2), 54–64. https://doi.org/https://doi.org/10.24260/add.v1i2.1113 Ratheeswari, K. (2018). Information Communication Technology in Education. Journal of Applied and Advanced Research, 3, S45–S47. https://doi.org/https://dx.doi.org/10.21839/jaar.2018.v3S1.169 Raza, M. Y., Khan, A. N., Khan, N. A., Ali, A., & Bano, S. (2020). Dark side of social media and academic performance of public sector schools students: Role of parental school support. Journal of Public Affairs, 20(3), 1–11. https://doi.org/10.1002/pa.2058 Rifa’i, A. (2016). Revitalisasi Fungsi Masjid Dalam Kehidupan Masyarakat Modern. Universum, 10(2), 155–163. https://doi.org/10.30762/universum.v10i2.256 Rosad, A. M. (2019). Implementasi Pendidikan Karakter Melalui Kegiatan Pembelajaran di Lingkungan Sekolah. Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 5(02), 173. https://doi.org/10.32678/tarbawi.v5i02.2074 Rumahuru, Y. Z. (2018). Ritual Sebagai Media Konstruksi Identitas : Suatu Perspektif Teoretisi. Dialektika: Jurnal Pemikiran Islam Dan Ilmu Sosial, 11(01), 22–30. https://doi.org/http://dx.doi.org/10.33477/dj.v11i1.1230 Sari, A. (2018). Pola Intervensi Pendidikan Dalam Pembinaan Kepada Pelajar Melalui Komunikasi Interkasional Bersumber Pada Simbol. Widya Komunika, 8(1), 117–133. https://core.ac.uk/download/pdf/287239106.pdf Setiyani, W. (2018). Keragaman Perilaku Beragama. Dialektika. Sholeh, Z. P. (2022). Learning Management in MI Miftahul Huda to Implement Character During The Implementation of Community Activity Restrictions. Iconie, 616–623. https://proceeding.iainpekalongan.ac.id/index.php/iconie/article/view/619 Stozek, J. M. M. (2021). Religious education teachers’ perspectives on character education. British Journal of Religious Education, 43(3), 349–360. https://doi.org/10.1080/01416200.2020.1713049 Sunandar, A. B. W. (2020). Strategi Kepala Sekolah dalam Menciptakan Budaya Religius di Sekolah. JAMP: Jurnal Adminitrasi Dan Manajemen Pendidikan, 3(2), 22–31. http://journal2.um.ac.id/index.php/jamp/ Suryana, D., Tika, R., & Wardani, E. K. (2022). Management of Creative Early Childhood Education Environment in Increasing Golden Age Creativity. 6th International Conference of Early Childhood Education. https://doi.org/10.2991/assehr.k.220602.005 Susilo, M. J., Dewantoro, M. H., & Yuningsih, Y. (2022). Character education trend in Indonesia. Journal of Education and Learning (EduLearn), 16(2), 180–188. https://doi.org/10.11591/edulearn.v16i2.20411 Suyitno, S. (2018). Strategi Pembentukan Budaya Religius Untuk Meningkatkan Karakter Islami di SD Muhammadiyah Wirobrajan 3 Yogyakarta. Edukasi Journal, 10(2), 191–204. https://doi.org/10.31603/edukasi.v10i2.2310 Syamaun, S. (2019). Pengaruh Budaya Terhadap Sikap dan Perilaku Keagamaan. At-Taujih : Bimbingan Dan Konseling Islam, 2(2), 81. https://doi.org/10.22373/taujih.v2i2.6490 Syukran, A. S. (2019). Fungsi Al-Qur’an bagi Manusia. Al-I‘Jaz, 1(2), 90–108. https://doi.org/https://doi.org/10.53563/ai.v1i2.21 Ulya. (2013). Ritus dalam Keberagamaan Islam: Relevansi Ritus dalam Kehidupan Masa Kini. Fikrah: Jurnal Ilmu Aqidah Dan Studi Keagamaan, 1(1), 195–206. https://doi.org/http://dx.doi.org/10.21043/fikrah.v1i1.312 Umar, I. (2020). Kiai As Al-Qudwah Al-Khasanah: the Role of Kiai in Shaping Religious Culture in Islamic Education Institution. Al-A’raf : Jurnal Pemikiran Islam Dan Filsafat, 17(2), 329–346. https://doi.org/10.22515/ajpif.v17i2.2995 Vermeulen, E. L. M. (2022). Assessing the impact of culture and creativity in society. Erasmus University Rotterdam, 114. Wahyuningsih, S. (2013). Metode Penelitian Studi Kasus; Konsep, Teori Pendekatan Psikologi Komunikasi, dan Contoh Penelitiannya. UTM PRESS. Yoenanto, M. M. H. (2022). Optimalisasi link and match sebagai upaya relevansi smk dengan dunia usaha dan dunia industri (DUDI). Jurnal Akuntabilitas Manajemen Pendidikan, 10(10), 27–37. https://doi.org/10.21831/jamp.v10i1.48008 Zahrudin, M., Ismail, S., Ruswandi, U., & Arifin, B. S. (2021). Implementasi Budaya Religius dalam Upaya Meningkatkan Kecerdasan Spiritual Peserta Didik. Asatiza: Jurnal Pendidikan, 2(2), 98–109. https://doi.org/10.46963/asatiza.v2i2.293